Kekerasan Dalam Rumah Tangga Dalam Perspektif Al Quran: Studi Pemikiran Amina Wadud - Sapri Ali; Achmad Asfi Burhanudin; Tahta Himayatir R (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Domestic violence (DV) is a crucial issue in modern society, especially for women, as it impacts physical, psychological, and spiritual suffering. In this context, the study of the verses of the Qur'an is important, especially by comparing the classical interpretation approach and the feminist hermeneutic approach of Amina Wadud. Amina Wadud, a feminist Muslim scholar, interprets the verses of the Qur'an by upholding the principles of justice and gender equality. This study uses a literature study method with a descriptive-analytical approach to examine Amina Wadud's thoughts on verses relevant to domestic violence. The results of this study, according to Amina Wadud, domestic violence, which is often legitimized, is not in line with the values ​​taught in the Qur'an, which is often understood literally, so that it often gives rise to misunderstandings regarding husband-wife relations. Although this interpretation is based on the authority of previous scholars, there is a need for a re-examination of the context of justice and equality as Islamic teachings.